1977
DOI: 10.2135/cropsci1977.0011183x001700010014x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Combining Ability and Heterosis in Converted Exotic Sorghums1

Abstract: The agronomic performance and breeding behavior of 11 restorer lines (R‐lines) derived from sorghum (Sorghum bicolor L. Moench) conversion program materials were evaluated in four environments in Iowa. Data for grain yield and the primary components of yield were obtained from single crosses and three‐way hybrids involving the R‐lines as male parents.For both types of hybrids, general combining ability (g.c.a.) effects of the R‐lines accounted for the largest portion of the variation expressed for grain yield,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…
and Pickett 1966, Laosuwan andAtkins 1977) and/or semi-arid Sorghum, Sorghum bicolor L. Moench, is grown mostly in semi-arid growing conditions (Jowett 1972, Kapran et al 1997). climates where unpredictable drought stress constitutes a major pro-Adaptation to drought stress may include drought escape, duction constraint.
…”
mentioning
confidence: 99%
“…
and Pickett 1966, Laosuwan andAtkins 1977) and/or semi-arid Sorghum, Sorghum bicolor L. Moench, is grown mostly in semi-arid growing conditions (Jowett 1972, Kapran et al 1997). climates where unpredictable drought stress constitutes a major pro-Adaptation to drought stress may include drought escape, duction constraint.
…”
mentioning
confidence: 99%
“…That method also has been used to alter the hydrocyanic In sorghum, Conner and Karper (1927) were among the first to observe that certain sorghum hybrids produced greater grain yields than their parents. Since that study, other studies with sorghum have shown that certain hybrids surpass their parents for grain yield (Karper and Quinby, 1937;Bartel, 1949;Stephens and Quinby, 1952;Quinby et al, 1958;Kambal and Webster, 1966;Niehaus and Pickett, 1966;Kirby and Atkins, 1968;Malm, 1968;Collins and Pickett, 1972;Laosuwan and Atkins, 1977;Wilson et al, 1978;Monyo et al, 1988). Heterotic manifestation also have been observed for increased plant height (Conner and Karper, 1927;Karper and Quinby, 1937;Bartel, 1949;Quinby et al, 1958;Kambal and Webster, 1966;Niehaus and Pickett, 1966;Kirby and Atkins, 1968;Laosuwan and Atkins, 1977)…”
Section: Results Of Selection In Random-mating Populationsmentioning
confidence: 92%
“…That value is approximately three times the 4.9% that was estimated by Lothrop (1983) for lAPlR sorghum population. Malm (1968) and Laosuwan and Atkins (1977) evaluated the performance of hybrid sorghums that involved either unadapted or exotic parental materials and found that additive gene effects were of major importance in the inheritance of seed size. However, investigations that involved parents that were more adapted to the area in dicated that nonadditive gene action also contributed appre ciably to the expression of seed size (Niehaus and Pickett, 1955;Beil and Atkins, 1957;Liang and Walter, 1968) Comparisons of the heritability estimates and genetic vari ances determined from the CO and C4 data may provide answers to these questions.…”
Section: Discussionmentioning
confidence: 99%